Disaster preparedness: older adults' perspectives. (2015) - Tuohy, R.; Stephens, C.; Johnston, D.
This paper focuses on age-specific disaster preparedness for older adults in order to reduce the disproportionate negative outcomes experienced by older adults during and after a disaster. Semi-structured interviews (16) were conducted in New Zealand with independent older adults living in the community. Thematic analysis provided rich detail about older adults' personal, social and cultural influences on preparedness. Age-specific challenges revealed practical and functional demands around the nature of preparedness actions associated with caring for a dependent spouse, reduced physical mobility, and loss of driving skills. Social networks and opportunities for interaction, together with socio-cultural norms of independence influenced how older adults negotiated disaster preparedness in non-disaster times. These results are discussed within a socio-cultural context, and suggest that age-specific planning for this vulnerable population group needs to account for the dual challenges older adults face: managing everyday independence, and personal responsibility for adopting and maintaining disaster preparedness.